2016
DOI: 10.1021/acs.iecr.6b01562
|View full text |Cite
|
Sign up to set email alerts
|

Third-Liquid Phase Transfer Catalysis for Horner–Wadsworth–Emmons Reactions of “Moderately Acidic” and “Weakly Acidic” Phosphonates

Abstract: Horner-Wadsworth-Emmons (HWE) reaction was investigated in green thirdliquid phase-transfer catalysis (TLPTC) system. With 6% equiv of the catalyst and 50% NaOH aqueous solution, the third phase was generated. In this TLPTC system, HWE reactions of benzaldehydes bearing electron-donating group with "weakly" or "moderately" acidic phosphonates proceeded in high yield (>90%) with all E-isomer product (stilbene). Teraoctyl ammonium bromide (TOAB) afforded a high yield of 93% for HWE reaction of benzaldehydes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…At the lower end of the reactor, a drain valve (19) was installed. Three feed vessels (24,25,26) were used to store each phase feed. Three single piston pumps (21,22,23) with pulse dampeners were used to pump each phase at the respective inlets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the lower end of the reactor, a drain valve (19) was installed. Three feed vessels (24,25,26) were used to store each phase feed. Three single piston pumps (21,22,23) with pulse dampeners were used to pump each phase at the respective inlets.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, there are reactions like esterification of potassium 4-methoxyphenylacetate [16], sodium benzoate [17], synthesis of n-butyl salicylate by esterification of sodium salicylate [18], benzoylation of sodium 4-acetylphenoxide [19], 4-chloro-3-methylphenol sodium salt [20], synthesis of butyl salicylate [21], benzyl salicylate [22], and ultrasound-assisted synthesis of dialkyl peroxides [23]. Recently, the Horner−Wadsworth−Emmons (HWE) reaction was studied using an L-L-L PTC system [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 To explore more green and practical reaction systems, Horner−Wadsworth−Emmons (HWE) reaction of various phosphonates proceeded in the TLPTC system in our previous research. 26,27 For HWE reaction of "weakly acidic" substrates in the TLPTC system, it was found that the bond-forming reaction occurred both in the third phase and the organic phase. Accordingly, the kinetics model containing the organic phase cycle and the third-phase cycle was proposed.…”
Section: Introductionmentioning
confidence: 99%